(untitled) (Journal of Scientific Research, 2017)
Over the past six decades, numerous demographers have studied fertility patterns of the states of India. These analyses portray a fertility decline rapid in some states and low or moderate in others. The present paper seeks to examine the potential factors responsible for regional demographic heterogeneity in the states of India based on empirical analysis of the birth counts for the period 1985-2011.This article establishes the interactive linkages between observed fertility and the changes in four principal potential causal forces such as literacy of parents and welfare initiatives by the government in the form of public expenditure and urbanisation drive. Among the individual effects female literacy is found to promote births significantly while higher male literacy is accompanied by lower occurrences of births. Government interventions and controls such as high infrastructure spending and urbanization process result in significantly reduced births. We utilize various spatial models to determine the diffusion effect of these factors on the fertility outcomes in the neighbouring interconnected regions and interpret them.